PROFIL KESALAHAN MAHASISWA PADA MATA KULIAH ANALISIS KOMPLEKS - Nely Indra Meifiani (Universitas Muhammadiyah Kotabumi, 2017)
This research is used to analyze the error profile encountered by STKIP PGRI Pacitan students in the course of Complex Analysis on the subject of PolarShape. The type of research used is qualitative descriptive. Subjects used as many as 2 students. Data collection methods used are test methods andinterview methods. The results of this study are on Misunderstanding, Transformation Errors and Process Errors. Misunderstanding is to assume thesymbol R = r when R ≠ r. Then assume that in calculating the root of the value of negative/positive just the same, even though the end result also remains the same. And it is often reversed between the values of x and y. Transformation error is inverted in determining x and y for cos arc formula. While the Process Error is unable to determine the magnitude of a special angle adjusted to the location of the point of z. weak in calculating the powers in the form of fractions. And wrong in drawing the z-point coordinates.